2009
DOI: 10.1038/nature07731
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the 5′→3′ exoribonuclease Rat1 and its activating partner Rai1

Abstract: The 5’→3’ exoribonucleases (XRNs) comprise a large family of conserved enzymes in eukaryotes with crucial functions in RNA metabolism and RNA interference1–5. XRN2, or Rat1 in yeast6, functions primarily in the nucleus and also plays an important role in transcription termination by RNA polymerase II (Pol II)7–14. Rat1 exoribonuclease activity is stimulated by the protein Rai115, 16. Here we report the crystal structure at 2.2 Å resolution of S. pombe Rat1 in complex with Rai1, as well as the structures of Rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
264
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(279 citation statements)
references
References 42 publications
13
264
1
1
Order By: Relevance
“…The mechanism underlying the inactivation of the exonuclease by this mutation at non-permissive temperature (above 34 C) is not well understood. As previously suggested from structural studies, 23 we found that this inactivation is in part due to the instability of the mutated protein. Indeed, as revealed by Western blot analyses shown in Fig.…”
Section: Nrd1p Is Not Involved In the Targeting Of Rho-induced Aberrasupporting
confidence: 65%
See 1 more Smart Citation
“…The mechanism underlying the inactivation of the exonuclease by this mutation at non-permissive temperature (above 34 C) is not well understood. As previously suggested from structural studies, 23 we found that this inactivation is in part due to the instability of the mutated protein. Indeed, as revealed by Western blot analyses shown in Fig.…”
Section: Nrd1p Is Not Involved In the Targeting Of Rho-induced Aberrasupporting
confidence: 65%
“…29 Thus, its implication in this alternative nuclear mRNP QC is conceivable. In contrast, our data indicate clearly that Rai1p, the Rat1p cofactor specialized in removing unmethylated caps, 23,24 is not involved in the production of uncapped HXK1 mRNPs since no transcript recovery could be observed in the rai1D strain (Fig. 5A).…”
Section: Discussioncontrasting
confidence: 52%
“…In both cases, inactivation of the exonuclease resulted in defects in termination, as measured by ChIP and/or nuclear run-on experiments, both methods measuring RNAPII density throughout transcribed genes. Rat1 and its cofactor Rai1 (see Xiang et al 2009) are strongly associated with the 39-end of genes, although in a manner independent of Ser2 CTD phosphorylation since a deletion of CTK1 does not affect their association (Kim et al 2004b). Recruitment of Rat1 is more likely indirect, through 39-end processing factors.…”
Section: Rat1/xrn2: the Transcription Termination Torpedomentioning
confidence: 99%
“…Previous work has identified the Rai1 protein as an enzyme that can function to remove the cap structure from mRNA in S. cerevisiae (25,26). In contrast to the Dcp1/Dcp2 complex that preferentially functions on a cap with an N7 methyl moiety and release m 7 Gpp, Rai1 preferentially targets mRNAs with unmethylated caps and releases the entire cap structure GpppN, although it can function on a methylated cap to release m 7 GpppN to a lesser extent (26).…”
Section: ′ P Ends Located In Intronsmentioning
confidence: 99%